1′-Acetoxychavicol acetate, a potent transient receptor potential ankyrin 1 agonist derived from Thai ginger, prevents visceral fat accumulation in mice fed with a high-fat and high-sucrose diet. Issue 10 (19th July 2021) - Ikeya, Tatsunori; Terada, Yuko; Morimitsu, Yasujiro; Kubota, Kikue; Ito, Keisuke; Watanabe, Tatsuo
ABSTRACT: 1′-Acetoxychavicol acetate (ACA) is found in Thai ginger ( Alpinia galanga ) and is a powerful agonist of transient receptor potential ankyrin 1 (TRPA1). In a diet-induced obesity mouse model, ACA reduced fat deposition. Sympathetic nerve activation was also indicated in the ACA-fed group. This study is expected to promote the utilization of food containing TRPA1 agonists to treat obesity.